Turn-on detection of cysteine by a donor-acceptor type quinoline fluorophore: Exploring the sensing strategy and performance in bioimaging - Muthusamy, Selvaraj; Zhao, Long; Rajalakshmi, Kanagaraj; Zhu, Dongwei; Soy, Rodah; Mack, John; Nyokong, Tebello; Wang, Shengjun; Lee, Kang-Bong; Zhu, Weihua (ELSEVIER SCI LTD, 2021)
Tracking the biothiol cysteine (Cys) in living systems is a significant responsibility to balance the redox environment and oxidative stress. A quinoline-7-nitro-1,2,3-benzoxadiazole (Q-NBD) fluorophore has been synthesized and characterized towards examination of Cys. The probe forms a quinoline-substituted phenol (Q-Ph-OH) after thiolysis of the NBD ether bond, leading to an increase of fluorescence at green channel. The turn-on sensing mechanism originates from the change in intramolecular charge transfer (ICT-OFF) along with an aggregationinduced emission (AIE) as suggested by spectroscopy measurements in solutions, time-dependent density-functional theory (TD-DFT) calculations and 1H NMR titration examination. Importantly, Q-NBD exhibited great sensitivity with a low limit of detection value of 89.5 nM and remarkable selectivity in various biothiols towards Cys. The sensor probe was successfully used for detecting both endogenous and exogenous Cys in PC3 living cells and spiked Cys in human urine samples.
Keywords: AGGREGATION-INDUCED EMISSION; FLUORESCENT-PROBE; SELECTIVE DETECTION; CYS